ASSESSMENT OF OCCUPATIONAL SAFETY AND HEALTH RISKS FOR WORKERS OPERATING CRANES ON THE SIGLI-BANDA ACEH TOLL ROAD PROJECT - Nasir, Muhammad; Ariscasari, Putri; Abdullah, Asnawi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: Operating a crane is a high-risk activity at a construction site. In addition to the potential for serious injuries or death, crane accidents can also result in significant property damage and impact to the project's budget and schedule. Crane accidents can also harm a company's reputation. This research aims to identify dangers and risks in crane work activities on the Sigli-Banda Aceh toll road project, especially section 3. Method: The research was conducted using observation, interviews, and the Job Safety Analysis (JSA) method. Risk analysis using semi-quantitative methods. The sample in this research were 2 Crawler Cranes, 2 Operators and 1 Supervisor.This research was conducted for 4 days from 16 to 19 October 2020. Results: The results of the Crane work activity assessment found 64.7% in the very high/extreme risk category, 23.52% in the high risk category, and 11.76% in the medium risk category. The high and very high/extreme risk value categories are found in lifting activities with identified risks are electric shock, falls from a height, broken bones, broken girders and fatalities. JSA is one of the tools used as a risk management effort. It is recommended that workers always attend the Tool Box Meeting and carry out each stage of work with JSA guidance. Recommendation: The advice given based on this research is to carry out control measures following the results of the hazard and risk assessment identified based on the JSA, carry out routine housekeeping, standby fire extinguishers on each crane, and provide shaded places considering that workers working in the field are exposed to heat exposure.